Genome-wide characterization of ubiquitin-conjugating enzyme gene family explores its genetic effects on the oil content and yield of Brassica napus - Yao, Shengli; Xie, Meili; Hu, Ming; Cui, XiaoBo; Wu, Haoming; Li, Xiaohua; Hu, Peng; Tong, Chaobo; Yu, Xiaoli (Frontiers in Plant Science, 2023)
Ubiquitin-conjugating enzyme (UBC) is a critical part of the ubiquitin–proteasome pathway and plays crucial roles in growth, development and abiotic stress response in plants. Although UBC genes have been detected in several plant species, characterization of this gene family at the whole-genome level has not been conducted in Brassica napus. In the present study, 200 putative BnUBCs were identified in B. napus, which were clustered into 18 subgroups based on phylogenetic analysis. BnUBCs within each subgroup showed relatively conserved gene architectures and motifs. Moreover, the gene expression patterns in various tissues as well as the identification of cis-acting regulatory elements in BnUBC promoters suggested further investigation of their potential functions in plant growth and development. Furthermore, three BnUBCs were predicted as candidate genes for regulating agronomic traits related to oil content and yield through association mapping. In conclusion, this study provided a wealth of information on the UBC family in B. napus and revealed their effects on oil content and yield, which will aid future functional research and genetic breeding of B. napus.